Evaluasi Kualitas Dan Harapan Pasien Terhadap Layanan Kesehatan Program Universal Health Coverage Di Puskesmas Ketapang Kabupaten Sampang - Susmiati Susmiati; Amirul Mustofa (Journal Of Social Science (JoSS), 2024)
The purpose of this study was to analyze the satisfaction of universal health coverage (UHC) program patients with health services at the Ketapang health center in Sampang district. Puskesmas Ketapang is one of the puskesmas in sampang district which includes the largest number of people registered in the universal health coverage program. This research method is descriptive with a qualitative approach where data collection techniques are carried out through direct interviews with medical personnel and also patients who come to visit the Puskesmas, documentation, observation, and data analysis. The results showed that patients (UHC) were very satisfied with the services provided from the puskesmas seen from reliability, responsiveness, assurance, empathy, but there were still patients who were less satisfied with the physical evidence or facilities provided at the Puskesmas. The results of the study seen from the dimension 5 gap there are no triggers for the gap, this shows that the quality of service that has been provided from the health center is good and in accordance with patient expectations.